1981
DOI: 10.1111/j.1365-246x.1981.tb02726.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between eruptions of Mount Etna, Sicily, and regional earthquakes as seen in historical records from AD 1582

Abstract: Catalogues from 1582 to the present of Etnean eruptions and earthquakes from various structural zones of southern Italy have been statistically compared using non-stationary Poisson statistics in order to search for correlative seismic and eruptive activity. A significant relationship exists between flank eruptions and earthquakes in the zone immediately surrounding the volcano. Also, crater eruptions are found to occur before flank eruptions which are not preceded by earthquakes. They do not, however, appear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 8 publications
1
23
0
Order By: Relevance
“…A tight time dependence between flank eruptions and both summit eruptions and earthquake swarms was also obtained, using a statistical approach, by Sharp, Lombardo & Davis (1981). Both summit eruptions and earthquake swarms were in fact found to precede, in a statistically significant way, the occurrence of flank activities.…”
Section: Discussion a N D Conclusionmentioning
confidence: 90%
“…A tight time dependence between flank eruptions and both summit eruptions and earthquake swarms was also obtained, using a statistical approach, by Sharp, Lombardo & Davis (1981). Both summit eruptions and earthquake swarms were in fact found to precede, in a statistically significant way, the occurrence of flank activities.…”
Section: Discussion a N D Conclusionmentioning
confidence: 90%
“…Mount Etna has displayed a variety of eruption styles, but since 1500 AD the activity has been predominately effusive eruptions from lateral vents on the volcanoes flanks, or from the central craters. While the catalogue of flank eruptions can be considered complete since 1535 (Wadge 1977), 1582 (Sharp et al 1981) or 1600 (Mulargia et al 1985), the corresponding date for summit eruptions is about 1970 (Wadge et al 1975). Moreover, the eruptive volume of pre‐1970 summit eruptions is impossible to measure accurately (Wadge et al 1975), and the quasi‐continuous nature of the activity makes the durations difficult to define, much less measure.…”
Section: Flank Eruptions At Mount Etnamentioning
confidence: 99%
“…Several studies have looked for a link between volcanic and seismic activity at Etna volcano (Sharp et al 1981; Nercessian et al 1991; Gresta et al 1994; De Rubeis et al 1997; Hirn et al 1997). Sharp et al (1981) and Nercessian et al (1991) performed statistical analyses using all eruptions and seismic events that occurred since 1582 within 200–300 km of the volcano, independent of their tectonic origin and magnitude. Depending on how they select the events, these authors obtained different results.…”
Section: Time Correlation Between Earthquakes and Eruptionsmentioning
confidence: 99%
“…Depending on how they select the events, these authors obtained different results. Sharp et al (1981) observed that earthquakes are related to flank eruptions in the area surrounding the volcano, with earthquakes preceding eruptions. However, Nercessian et al (1991), found that earthquakes mainly occurred at the end of eruptive periods.…”
Section: Time Correlation Between Earthquakes and Eruptionsmentioning
confidence: 99%